Supporting Sustainable Livelihoods through Wildlife Tourism - Twining-Ward, Louise (World Bank, Washington, DC, 2018)
Tourism is an engine for jobs, exports, and investments. The tourism sector is also the largest, global, market-based contributor to financing protected area systems. Nature-based tourism (NBT) is a sub-component of the tourism sector that includes wildlife-based tourism. NBT is a powerful tool countries can leverage to grow and diversify their economies while protecting their biodiversity, and contributing to many sustainable development goals (SDG), including SDGs 12 and 15. Local communities, private sector enterprises, and governments can also benefit from investments in tourism through increased market opportunities and linkages to tourism services such as agriculture production, hoteling, restaurants, transportation, health services, etc. This report explores innovative tourism partnership and investment opportunities to help countries unlock smart investment and grow tourism sustainably. It showcases sustainable wildlife tourism models from Botswana, India, Kenya, South Africa and many other countries and promotes solutions that offer insight into the wildlife based tourism sector as a mechanism for inclusive poverty reduction and global conservation.